Running performance of substitutes in the FIFA World Cup after the change in substitution rule: influence of match outcome, playing position and sex - Wei, X.; Zhang, R.; Maitiniyazid, A.; Chmura, P.; Randers, M. B.; Krustrup, P. (International Journal of Performance Analysis in Sport, 2024)
This study intended to investigate the impact of substitution rule change on the physical performance in World Cup tournaments. Running data from the 2022 and 2023 FIFA World Cups were used for analysis. The results show that substitutes have much more sprinting, high-speed running and moderate speed running per minute than starters (p < 0.05), with similar magnitudes of differences for the men`s (28.4-47.6%) and women`s World Cup (23.4-59.5%). Substitutes in winning vs losing teams had higher sprint distance (3.7 vs 2.8 m· min-1) and number of high-speed running (1.70 vs 1.58 times· min-1) in men`s World Cup and higher sprint distance (3.3 vs 2.5 m· min-1) in women`s World Cup. In the men`s World Cup, substituted midfielders had a higher frequency and greater distance covered with high-speed running (1.85 vs 1.57 and 1.44 times· min-1; 10.1 vs 8.9 and 7.8 m· min-1) and higher sprint frequency (0.74 vs 0.71 and 0.62 times· min-1) compared to forwards and defenders, which was not the case for the Women`s World Cup. Together, this study underlines the importance of substitutions for the team running performance in modern elite football under the new substitution rules, and practitioners need to pay attention to the use of substitute players under the new rules.